2011
DOI: 10.1063/1.3541249
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of nitrogen oxides on graphene and graphene oxides: Insights from density functional calculations

Abstract: The interactions of nitrogen oxides NO(x) (x = 1,2,3) and N(2)O(4) with graphene and graphene oxides (GOs) were studied by the density functional theory. Optimized geometries, binding energies, and electronic structures of the gas molecule-adsorbed graphene and GO were determined on the basis of first-principles calculations. The adsorption of nitrogen oxides on GO is generally stronger than that on graphene due to the presence of the active defect sites, such as the hydroxyl and carbonyl functional groups and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
111
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(125 citation statements)
references
References 58 publications
13
111
1
Order By: Relevance
“…Few theoretical studies of gas molecular adsorption on GO have also been reported [60,61]. The adsorption of ammonia on graphene and graphene oxide investigated using first-principles calculations showed that the surface active sites such as epoxy and hydroxyls on GO surface enhanced the interactions between NH3 and GO.…”
Section: Graphenementioning
confidence: 99%
See 1 more Smart Citation
“…Few theoretical studies of gas molecular adsorption on GO have also been reported [60,61]. The adsorption of ammonia on graphene and graphene oxide investigated using first-principles calculations showed that the surface active sites such as epoxy and hydroxyls on GO surface enhanced the interactions between NH3 and GO.…”
Section: Graphenementioning
confidence: 99%
“…Graphene oxide, single-or few layered-graphite oxide sheets obtained by chemical oxidation of graphite and subsequent exfoliation in water, are rich in oxygen-containing groups such as epoxies, hydroxyls, carboxyls, etc., on its basal planes and edges which makes it a versatile material for gas detection [58][59][60][61]. Prezioso and his co-workers [58] proposed a practical and highly sensitive gas sensor based on large and highly oxidized GO flakes prepared by modified Hummers' method.…”
Section: Graphenementioning
confidence: 99%
“…Using the same approach, the adsorption of nitrogen oxide on graphene and GO has been addressed in Ref. 12, and the mechanical properties of both ordered and amorphous GO have been investigated in Ref. 13.…”
mentioning
confidence: 99%
“…176 In their study, they showed that the defect sites in GO (i.e. carbonyl and hydroxyl) increase the binding energies of the nitrogen oxides as well as enhancing the charge transfer from the nitrogen oxides which in turn leads to chemisorption.…”
Section: Reactive Gas Adsorptionmentioning
confidence: 99%